2022
DOI: 10.18805/ijar.bf-1414
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight Relationship and Fecundity of Parastromateus niger from Gwadar Port Balochistan Province, Pakistan

Abstract: Background: Parastromateus niger, is one of the important fish species from economic point of view in Gwadar, Balochistan-Pakistan. This study was carried out to determine the growth and fecundity of Parastromateus niger. Methods: Growth of P. niger was determined by applying Le Cren formula while mean fecundity and relative fecundity of this fish was calculated by using equation of Yelden and Avsar. Result: Relationship between fish weight and ovary weight was found as 0.384 and 0.898 respectively in 1st and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In this linking, maintaining control of Gwadar guarantees shipping over the current routes. Additionally, it makes it easier to keep an eye on Indian navy operations, US naval operations in the Persian Gulf, and Indo-US maritime cooperation in the Indian Ocean (Siddique, 2023).…”
Section: China's Intentionsmentioning
confidence: 99%
“…In this linking, maintaining control of Gwadar guarantees shipping over the current routes. Additionally, it makes it easier to keep an eye on Indian navy operations, US naval operations in the Persian Gulf, and Indo-US maritime cooperation in the Indian Ocean (Siddique, 2023).…”
Section: China's Intentionsmentioning
confidence: 99%
“…Further differences are influenced by various circumstances, including food, stress brought on by crowding, or the reproductive cycle (Oyebamiji et al, 2008). The current study aims to add and complement already-existing knowledge about the shrimp growth pattern (Siddique et al, 2022). To manage shrimp resources sustainably and also give relevant information on the length-length, length-weight connection (growth patterns) and condition factor on shrimps caught in coastal waters from the southeast coast of Tamil Nadu (Suryanti et al, 2018;Olawusi et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, Vandana et al (2021) reported on hepatic microsporidiosis in brackish water fish, highlighting the presence of parasites in marine environments and their implications for fish health (9). Mehar et al (2022) expanded this understanding by observing the levels of heavy metals in fish tissues from the Karachi and Gwadar coasts of Pakistan, concluding that the Karachi environment was more polluted due to industrial activities and heavy sea traffic (10,11). The integration of these studies paints a comprehensive picture of the challenges facing marine ecosystems, particularly in the context of pollution and its impact on fish health (12,13).…”
Section: Introductionmentioning
confidence: 99%